First- versus last-year university students’ physical education motivations - Irkhin, V.N.; Gut, Y.N.; Korneeva, S.A.; Rylsky, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey and analyze physical education motivations of the first- versus last-year university students not majoring in sports. Methods and structure of the study. Belgorod State National Research University’s Psychology Department students (n= 98) were sampled for the survey run in 2021. They were subject to My Attitude to Physical Education questionnaire survey by Y.N. Gut, S.A. Korneeva; Sports Motivations test by A.V. Shaboltas; and the Personality Success Motivations and Failure Avoidance tests by T. Ehlers. The survey data were processed by the standard statistical toolkit with the nonparametric Mann-Whitney U-test for unrelated samples using the SPSS 25 software. Results and conclusion. The study was designed to survey and analyze physical education motivations of the first- versus last-year university students. We found the first-year students more physically active, although the seniors were tested trained on a more regular and determined basis knowing the benefits of physical education for health, mood and wellbeing. The younger group was tested focused on the socializing, peer communication, friends-making, public approval and recognition aspects. As for the GTO Complex test motivations, the seniors are reportedly more focused on success. The survey data and analysis found the genuine physical education motivations being volatile and underdeveloped in the younger group majoring not majoring in sports.